Assessing Theories and Strategies Regarding Career Transition for Students with Visual Impairments - Chiedu Eseadi (South Sulawesi Education Development (SSED), 2023)
The purpose of this paper is to examine evidence-based theories and strategies that can aid in comprehending and fostering the career transitioning of students with visual impairments. Understanding the various career transitioning theories will enable career professionals and visually impaired students to achieve a successful career counselling encounter. The suggested theoretical models highlight the importance of psychological and social variables in predicting a successful transition and the attainment of good and meaningful jobs by visually impaired students. The theories discussed in this paper include Schlossberg's transition theory; Bridges’ transition framework; Psychological model for student retention; Psychology of working theory; Opportunity structure theory; Liquid modernity and life design; and Career construction theory. This article contributes to the literature on career counselling by arguing and elucidating the theoretical significance of these vocational counselling theories and strategies as they pertain to promoting career transition for visually impaired students. Theoretical knowledge could help to inform counselling methods and enable professionals, and various institutions to understand the contextual drivers of career transitioning, advocate for more inclusive workplaces, and explore solutions to reduce the number of unemployed visually impaired graduates. Career counsellors can adapt many techniques if they use an integrated theoretical approach to help visually impaired students transition from school to their potential employment.